2001
DOI: 10.1034/j.1399-0004.2001.600609.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial Down syndrome: evidence supporting cytoplasmic inheritance

Abstract: The frequently observed familial aggregation of Down syndrome (DS) 47,+21 and other aneuploidies and the phenomenon of double aneuploidy involving DS cannot be accounted for by chance alone. To clarify possible aetiological factors, pedigrees from all 7 affected families with repeated marriages referred to two regional genetics centres were examined. In each case the recurrence of aneuploidy was on the mother's side (p<0.01). Such a pattern suggests cytoplasmic inheritance of a risk factor. The hypothesis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Moreover, defects in mitochondrial function appear to contribute to chromosomal nondisjunction and age-related trisomies such as Down's syndrome (Schon et al, 2000;Arbuzova et al, 2001Arbuzova et al, , 2002. Other studies have demonstrated that postmeiotic fertility and developmental defects can be caused by abnormal mitochondrial morphology in mammals (Van Blerkom et al, 2000;Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, defects in mitochondrial function appear to contribute to chromosomal nondisjunction and age-related trisomies such as Down's syndrome (Schon et al, 2000;Arbuzova et al, 2001Arbuzova et al, , 2002. Other studies have demonstrated that postmeiotic fertility and developmental defects can be caused by abnormal mitochondrial morphology in mammals (Van Blerkom et al, 2000;Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Further, a two to three times increased risk of Down syndrome in the siblings of affected individuals was observed, after accounting for selection bias (Penrose 1954). A recent study by Arbuzova and colleagues on familial cases of Down syndrome showed that while there is a greater recurrence risk for younger women, by the age of 40, the recurrence risk is not significantly different from non-familial cases (Arbuzova et al 2001). Notably, a history of Down syndrome miscarriage also increases the risk of other fetal aneuploidies in subsequent pregnancies (Bianco et al 2006).…”
Section: Penrose and Parental-age Effects In Down Syndromementioning
confidence: 94%
“…(30,31) Furthermore mtDNA is almost entirely of maternal origin, as is the extra chromosome 21 in the vast majority of DS cases, and examination of pedigrees from families with aneuploidy recurrence indicates cytoplasmic inheritance of a risk factor. (27) Mutations in mtDNA may bring about an increase in the generation of free-radicals and reduce ATP levels. This, in turn, could affect the synaptonemal complex, chromosome segregation and division spindle, alter recombination (the enzymes participating in recombination and DNA repair are ATPdependent) (32,33) and so lead to aneuploidy.…”
Section: Sod-1 and Abpp-gene Dosage Effects Or Protective Response?mentioning
confidence: 99%
“…We have also suggested that mtDNA mutations may have a role in the aetiology of DS (15,16,26) and subsequently supportive evidence has accumulated. (27,28) It is well-established that, as for the risk of DS, the number of mtDNA mutations increases with age in different cells, such as oocytes. (29) In addition, mtDNA mutations are known to be associated with AD and diabetes, (24) which are more common in the mothers of DS individuals.…”
Section: Sod-1 and Abpp-gene Dosage Effects Or Protective Response?mentioning
confidence: 99%